(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Anterior cruciate ligament (ACL) reconstruction is a commonly performed orthopedic procedure aimed at restoring knee stability and functional performance following ligament injury. The choice of graft plays a crucial role in determining postoperative outcomes. Despite advancements in surgical techniques, the optimal graft choice remains controversial. Objectives: This study aimed to evaluate and compare the functional outcomes and complication rates associated with different graft types used in ACL reconstruction. Methods: A prospective observational study was conducted at a tertiary care centre in Dindigul from January 2023 to December 2025. A total of 148 patients with ACL injury were assessed, of which 120 patients met the inclusion criteria. Patients were categorized into three groups based on graft type: hamstring tendon (HT), bone–patellar tendon–bone (BPTB), and quadriceps tendon (QT). Functional outcomes were evaluated using the Lysholm Knee Score and International Knee Documentation Committee (IKDC) score preoperatively and at 6 months and 12 months postoperatively. Statistical analysis was performed using appropriate tests, and a p-value < 0.05 was considered significant. Results: The mean age of patients was 28.4 ± 6.2 years, with a male predominance (75%). Hamstring grafts were most commonly used (50%), followed by BPTB (30%) and QT (20%). All groups demonstrated significant improvement in functional scores compared to preoperative values (p < 0.001). The BPTB group showed slightly higher Lysholm and IKDC scores, indicating better knee stability. However, anterior knee pain was more common in the BPTB group. The HT group showed fewer donor site complications, while QT grafts demonstrated comparable functional outcomes with moderate complication rates. Conclusion: ACL reconstruction using different graft types results in significant improvement in knee function and stability. While BPTB grafts offer superior stability, they are associated with higher donor site morbidity. Hamstring and quadriceps tendon grafts provide comparable outcomes with fewer complications. Although the study reports outcomes at 12 months follow-up, these findings provide early insight into long-term functional trends. Individualized graft selection remains essential for optimal patient outcomes.